2019
DOI: 10.1021/acschemneuro.9b00331
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Assessment of Retinal Biomarkers by Hyperspectral Imaging: Early Detection of Alzheimer’s Disease

Abstract: A noninvasive and cost-effective means to detect preclinical Alzheimer’s disease (AD) and monitor disease progression would be invaluable. The retina is a developmental extension of the brain and has been viewed as a window to evaluate AD-related pathology. Cross-sectional studies have shown structural changes in the retina of AD patients that include thinning of the retinal nerve-fiber layer and changes in retinal vasculature. However, such changes do not manifest in early stages of the disease nor are they s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 35 publications
0
54
0
Order By: Relevance
“…Retinal imaging scores correlated with Aβ burden in the brain (Hadoux et al, 2019). Intriguingly, a similar study from More and colleagues, the team that initially developed the rHSI technique in murine models (More and Vince, 2015;More et al, 2016), found the largest deviation in rHSI signatures between MCI patients and controls, irrespective of other ocular conditions such as cataracts or glaucoma (More et al, 2019). The same technique was able to distinguish cerebral Aβ+ subjects from Aβ− subjects with 85% accuracy based on retinal vascular measures including vessel tortuosity and diameter (Sharafi et al, 2019).…”
Section: Retinal Imagingmentioning
confidence: 83%
“…Retinal imaging scores correlated with Aβ burden in the brain (Hadoux et al, 2019). Intriguingly, a similar study from More and colleagues, the team that initially developed the rHSI technique in murine models (More and Vince, 2015;More et al, 2016), found the largest deviation in rHSI signatures between MCI patients and controls, irrespective of other ocular conditions such as cataracts or glaucoma (More et al, 2019). The same technique was able to distinguish cerebral Aβ+ subjects from Aβ− subjects with 85% accuracy based on retinal vascular measures including vessel tortuosity and diameter (Sharafi et al, 2019).…”
Section: Retinal Imagingmentioning
confidence: 83%
“…43,78,79 The same authors select retinal regions of interest and compare optical densities in different stages of AD in humans. 81 Alternatively, rather than directly observing differences in spectra, Hadoux et al 56 semiautomatically extracted average spectra from regions of interest in the retinal image and feed these as input into a classification model. A variant of linear discriminant analysis produces a "hyperspectral score" that is assumed to be an estimate for retinal amyloid load.…”
Section: Hyperspectral Data Processingmentioning
confidence: 99%
“…When adapted for in vivo human use, an inverse correlation with the Mini-Mental State Exam score was also seen in those lower wavelengths (430-580 nm). 81 Hadoux et al 56 successfully trained a classifier to distinguish between amyloid positron emission tomography positive human participants compared with controls based on the hyperspectral signature of the retina. Last, Sharafi et al 61 reported a significant hyperspectral difference between retinal tissue (containing vessels) in amyloid positive individuals compared with amyloid negative ones.…”
Section: Admentioning
confidence: 99%
See 1 more Smart Citation
“…This imaging spectroscopy technique is based on the fact that soluble Aβ aggregates -most likely Aβ42 -interfere with traversing light, leading to Rayleigh light scattering and a characteristic hyperspectral signature, the magnitude of which appear to be proportional to the amount of Aβ present 9,10 . In the past year, following promising post mortem and in vivo studies in both animal and human retinas 9,10,43 , results of the first clinical trial showing that in vivo retinal hyperspectral imaging can discriminate between Aβ PET-positive cases and controls emerged 27 . This, together with our data, suggests that hyperspectral imaging can be used to monitor retinal Aβ accumulation, with the potential to provide quantitative measures of Aβ oligomers.…”
Section: Discussionmentioning
confidence: 99%